Oral Presentations Abstracts: THE ROLE OF RESEARCH ETHICS COMMITTEES: MAKING A FAIR OFFER - SHEEHAN, Mark (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 In this paper, I engage with the on-going debate about the nature of the task that research ethics committees (RECs) have in coming to assess the ethics of research proposals. Some have argued that the role of RECs is to protect participants from harm in the context of researchers who want to benefit future people. Others have argued that the role of RECs is primarily to ensure that potential participants are provided with full information – enough to make an informed choice. On this later view, RECs protect choice rather than restrict it. I argue that both of these orientations are mistaken and that the role of RECs more akin to a societal overseer who ensures that the research is worthwhile and, most importantly, that it presents a fair offer to potential participants. On this view, the REC’s role is to balance potential harms to participants with the potential benefits of the research in the context of presenting the choice about whether to participate to potential participants.